2010
DOI: 10.3109/14767058.2010.529971
|View full text |Cite
|
Sign up to set email alerts
|

Documentation improvements following multidisciplinary educational program on electronic fetal heart rate tracings

Abstract: Incorporating evidence-based strategies for systemic change is an important step in program development in obstetrics. A multifaceted, multi-disciplinary program with frequent audits and feedback can yield high compliance in adoption of guidelines and result in practice change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…45,62,63,71,73 The actual numbers participating in each of the studies were often not reported or were unclear. 26,41,44,45,49,50,53,60,[62][63][64][69][70][71][72][73][74]77,78,84 Where participant numbers were reported, they varied from six 51,75 to 4439 81 individuals.…”
Section: Participantsmentioning
confidence: 99%
“…45,62,63,71,73 The actual numbers participating in each of the studies were often not reported or were unclear. 26,41,44,45,49,50,53,60,[62][63][64][69][70][71][72][73][74]77,78,84 Where participant numbers were reported, they varied from six 51,75 to 4439 81 individuals.…”
Section: Participantsmentioning
confidence: 99%
“…Our successful approach may serve as a template for future widespread practice changes that are needed in Labor and Delivery units, whether they are driven by new evidence, regulatory pressures, workflow issues, or a combination of these factors. This approach also was successful in our institution when implementing a large-scale process change with the transition to the use of fetal heart rate tracing categories [15]. Several studies have shown that administering antibiotics before skin incision resulted in lower incidence of infectious complications following cesarean delivery [9,10,13].…”
Section: Discussionmentioning
confidence: 96%
“…We addressed the first factor, standardization in interpretation and management of fetal heart rate tracings, in the following ways: 36 We removed “failure to perform a cesarean delivery for non-reassuring fetal heart rate tracing” from our quality measures for our peer review committee and stopped providing provider feedback on this indicator.We educated providers on the use of category systems to describe fetal heart rate tracings. Large posters and pocket cards with category nomenclature and details of each category were available for reference.…”
Section: Methodsmentioning
confidence: 99%